Provision of Lipid-Based Nutrient Supplements to Mothers During Pregnancy and 6 Months Postpartum and to Their Infants from 6 to 18 Months Promotes Infant Gut Microbiota Diversity at 18 Months of Age but Not Microbiota Maturation in a Rural Malawian Setting: Secondary Outcomes of a Randomized Trial. Issue 4 (7th January 2020) - Kamng'ona, Arox W; Young, Rebecca; Arnold, Charles D; Patson, Noel; Jorgensen, Josh M; Kortekangas, Emma; Chaima, David; Malamba, Chikondi; Ashorn, Ulla; Cheung, Yin B; Ashorn, Per; Maleta, Kenneth; et al.
ABSTRACT: Background: Diet may alter the configuration of gut microbiota, but the impact of prenatal and postnatal nutritional interventions on infant gut microbiota has not been investigated. Objective: We evaluated whether providing lipid-based nutrient supplements (LNSs) to mother–infant dyads promotes a more diverse and mature infant gut microbiota, compared to maternal supplementation with multiple micronutrients (MMN) or iron and folic acid (IFA). Methods: We enrolled 869 pregnant women in a randomized trial in Malawi. There were 3 study groups, with women receiving 1 MMN capsule daily during pregnancy and 6 mo postpartum, or 1 LNS sachet (20 g) daily during pregnancy and 6 mo postpartum, or 1 IFA capsule daily (during pregnancy) then a placebo daily (postpartum). Infants in the LNS group received LNS from 6 to 18 mo; infants in the other groups did not receive supplements. The infants' fecal microbiota were characterized by PCR amplification and sequencing of the bacterial 16S rRNA gene (variable region 4). The primary outcomes were microbiota α diversity and maturation [as microbiota-for-age z score (MAZ)]. Specific associations of taxa with intervention were established with indicator species analysis (ISA). Results: Primary outcomes did not differ between IFA and MMN groups, so these groups were combined (IFA + MMN). Mean ± SD α diversity was higher in the LNS group at 18 mo for Shannon index [3.01 ± 0.57 (LNS) compared with 2.91 ± 0.60 (IFA + MMN), P = 0.032] and Pielou's evenness index [0.61 ± 0.08 (LNS) compared with 0.60 ± 0.09 (IFA + MMN), P = 0.043]; no significant differences were observed at 1, 6, 12, or 30 mo. MAZ and β diversity did not differ at any age. We found 10 and 3 operational taxonomic units (OTUs) positively associated with LNS and IFA + MMN, respectively; however, these associations became nonsignificant following false discovery rate correction at 10%. Conclusions: Prenatal and postnatal LNS intake promoted infant gut microbiota diversity at 18 mo, after 12 mo of child supplementation, but did not alter microbiota maturation. This trial was registered at clinicaltrials.gov as NCT01239693.